Global, regional, and national burden of fracture of pelvis, 1990–2021: analysis of data from the Global Burden of Disease Study 2021 - Wei, Jiyong; He, Dezhi; Lan, Guipeng; Xu, Minglian; Guo, Jianfeng; Lan, Yanni; Zong, Shaohui (Frontiers in Public Health, 2025)
BackgroundFractures of the pelvis are significant orthopedic injuries associated with high morbidity, mortality, and substantial economic burden worldwide.MethodsThis study aimed to comprehensively analyze the disease burden of pelvic fractures globally from 1990 to 2021 using data from the Global Burden of Disease (GBD) Study 2021. First, we conducted a descriptive analysis in 2021, stratifying data by subtypes. Secondly, we used the Linear regression models to analyze temporal trends. Finally, we used two models to predict the future burden. Furthermore, we examined the correlation between estimated annual percentage change (EAPCs) and age-standardized rates (ASRs), as well as Human Development Index (HDI) scores in 2021.ResultsIn 2021, pelvic fractures caused 4,524,448 incident cases (95% UI 3,283,345–6,583,735), 13,100,257 prevalent cases (12,103,233–14,174,613), and 2,241,606 years lived with disability (YLDs; 1,559,349–2,965,288). The age-standardized incidence rate (ASIR) was 56.00 per 100,000 (40.96–81.22), age-standardized prevalence rate (ASPR) 155.97 (143.85–168.87), and YLDs rate 26.74 (18.59–35.36). Rates were higher in males, with ASIR, ASPR, and YLDs 1.14, 1.35, and 1.37 times those in females. Age-specific ASRs rose with age. Australasia had the highest ASIR (148.39; 101.02–219.91), and the Commonwealth Low-Income region the lowest (21.97; 16.86–29.23). Western Africa recorded the lowest ASPR (77.37; 70.44–86.42) and YLD rate (13.34; 9.39–18.00). Nationally, ASIR was highest in Andorra (176.62; 111.81–281.70) and lowest in Kiribati (17.96; 13.88–23.10). Projections suggest rising burden through 2046. EAPCs were inversely associated with ASRs and HDI, except for a weak, non-significant positive correlation with ASIR (ρ = 0.08; P = 0.27).ConclusionOur findings reveal a substantial and increasing global burden of pelvic fractures, particularly in regions with limited access to high-quality trauma care. The increasing proportion of years lived with disability (YLDs) due to long-term disability underscores the importance of comprehensive management strategies, including prevention, timely treatment, and effective rehabilitation.